Diagnostic role of fine needle aspiration cytology in breast lesion (Journal of Pathology of Nepal, 2024)
Background: Breast lesions are among the most common concerns presenting in surgical outpatient departments, often accompanied by anxiety over potential malignancy. Fine needle aspiration cytology offers a safe, reliable, and efficient diagnostic procedure that minimizes patient discomfort while providing rapid results.Materials and Methods: This hospital-based descriptive study was conducted in the Department of Pathology at Nepal Medical College Teaching Hospital over one year (August 2023 to July 2024) following ethical approval from the Institutional Review Committee. A total of 94 patients presented with breast lesions were included in the study. Cytology samples were collected through fine needle aspiration cytology, which was performed on each patient after obtaining written consent. The data was then entered and analyzed using the Statistical Package for Social Sciences (SPSS) version 17.0.Results: A total of 94 cases were enrolled in this study. The highest occurrence of breast lesions was observed in the 31–40 years age group. Benign breast lesions were more common in younger individuals, while malignant lesions were predominantly seen in older age groups. Benign breast lesions were more common in the left breast and the upper outer quadrant was the most commonly affected site. Out of 94 breast lumps, 11 cases (11.7%) were malignant and 83 (88.2%) cases were benign.Conclusion: Fine needle aspiration cytology serves as a secure and easy method for diagnosing breast lesions with minimal invasiveness.